From Ritual to Virtual: Enhancing Hindu Religious Education through Digital Literacy - Suciartini, Ni Nyoman Ayu; Darmini, Darmini; Payuyasa, I Nyoman (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
This study highlights the ideal ratio between the number of lecturers and students in Islamic Education classes at the Faculty of Economics, Udayana University, Bali. With only one lecturer teaching 200 students, this imbalance is a significant concern, especially amidst worries about the spread of extremism and exclusivism on campus. The research aims to evaluate the learning process, religious moderation attitudes among lecturers and students, and factors influencing religious moderation attitudes among students. Using a qualitative descriptive method and a case study design, data were collected through observation, in-depth interviews, and questionnaires, and analyzed using descriptive analysis techniques. The findings indicate that the ratio of Islamic Education lecturers to students does not meet government standards, despite the implementation of various teaching methods. Nevertheless, attitudes towards religious moderation are generally positive, although there are indications of a lack of moderation among some students. Internal and external factors were identified as influencing factors on religious moderation attitudes. These findings emphasize the need for ongoing efforts to improve the quality of Islamic Education learning through enhancing lecturer competencies and implementing programs to strengthen religious moderation in higher education, aiming to promote tolerance and reinforce religious moderation among students.